Asymmetric Au-core Pd-shell nanoparticles supported on reduced graphene oxide for enhanced electrocatalytic activity. Issue 87 (6th September 2016) - Noh, Sungmin; Shim, Jun Ho
Abstract : Asymmetric Au-core Pd-shell nanoparticles supported on rGO simply prepared by a GRR-like technique exhibit superior ORR performance compared to commercial Pt/C. Abstract : Reduced graphene oxide (rGO)-supported asymmetric Au-core Pd-shell bimetallic nanoparticles (AuPd/rGO), i.e. Pd 2+ is reduced only on the exposed Au(0) nanoparticle (GN) surface, were prepared using a simple two-step synthetic approach. First, negatively charged ∼15 nm GNs were prepared and attached to the amine-functionalized positive surface of a glass slide. Second, the substrate of the adsorbed Au-core nanoparticles was added to the Pd precursor solutions (0.5, 5, and 10 mM of PdCl2, respectively), resulting in the deposition of a thin asymmetric Pd layer on the surface of the GNs via a tailored galvanic replacement reaction (GRR). This led to more sophisticated structures such as asymmetric core–shell nanoparticles, while avoiding monometallic nanoparticle formation. The compositional/structural features were characterized by high-resolution transmission electron microscopy, scanning TEM, UV-Vis spectroscopy, X-ray diffraction, and X-ray photoelectron spectroscopy. The catalytic activity of AuPd/rGO was investigated by rotating disk electrode voltammetry in 0.1 M NaOH. In particular, AuPd/rGO with a Au : Pd wt% ratio of 0.61 : 0.39 showed superior oxygen reduction reaction (ORR) activity along with satisfactory stability under alkaline conditions.